2019
DOI: 10.11152/mu-2001
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between epicardial adipose tissue and arterial stiffness in patients with rheumatoid arthritis

Abstract: Aim: To evaluate the relationship between epicardial adipose tissue (EAT) and arterial stiffness (AS) in patients with rheumatoid arthritis (RA), considering cardiovascular risk factors and disease characteristics.Material and methods: A total of 84 RA patients were included in this cross-sectional study. EAT and carotid intima-media thickness (cIMT) were measured ultrasonographically while aortic pulse wave velocity (aPWV), the main AS parameter, was determined using an oscillometric device.Results: Mean dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
(49 reference statements)
1
4
1
Order By: Relevance
“…In our study, we did not observe any correlation between EATT and disease duration. Similar results were also found in other studies which reported that the progression of the disease does not result in a signi cant increase in EATT [31,44]. These results may be interpreted as disease activity, rather than disease duration, has a greater in uence on increasing the risk of cardiovascular events, even in the early stages of the disease.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, we did not observe any correlation between EATT and disease duration. Similar results were also found in other studies which reported that the progression of the disease does not result in a signi cant increase in EATT [31,44]. These results may be interpreted as disease activity, rather than disease duration, has a greater in uence on increasing the risk of cardiovascular events, even in the early stages of the disease.…”
Section: Discussionsupporting
confidence: 89%
“…A cross-sectional study conducted with a cohort of 34 female RA patients and 16 controls matched for age and body mass index (BMI) showed greater EAD thickness in female patients with RA. Another age-and sex-matched cross-sectional study, including 76 patients with RA and 50 controls, reported a greater EAD thickness in RA patients (26,27). Increased EAD thickness is associated with endothelial dysfunction in spondyloarthritis (28).…”
Section: Discussionmentioning
confidence: 97%
“…Similar results were also obtained by Kim et al in a study in which EAT thickness was associated with arterial stiffness determined by pulse wave velocity [ 39 ]. EAT thickness was also correlated with arterial stiffness measured by pulse wave velocity in patients with rheumatoid arthritis [ 40 ]. Furthermore, Argan et al associated EAT thickness with the risk of ascending aortic dilatation [ 41 ] and similar results were obtained in a study by Canga et al [ 42 ].…”
Section: Discussionmentioning
confidence: 99%